Eksperimentasi Model Pembelajaran Kooperatif Tipe Team Assisted Individualization Guide Note Taking (TAI GNT) Ditinjau dari Kemandirian Belajar Siswa - Gazali, Muhammad (Jurnal Elemen, 2015)
The aim of the research was to determine the effect of learning models on mathematics learning achievement viewed from students independence learning. The learning models compared were cooperative learning model of TAI GNT, cooperative learning model of TAI, and conventional model. The type of the research was a quasi-experimental research. The population was the tenth grade students of senior high school at East Lombok. The results of this research are as follows. (1) In each level of independence learning (high, medium, and low), TAI GNT model gives better mathematics learning achievement than TAI and conventional model, besides, TAI model gives better mathematic learning achievement than conventional model. (2) In each learning models (TAI GNT, TAI and conventional), the students with high independence learning have better mathematics learning achievement than the students with medium and low independence learning, and the students with medium independence learning have the same mathematics learning achievement as the students with low independence learning.